Emerging Technologies in Arthroplasty: Additive Manufacturing - Banerjee, Samik; Kulesha, Gene; Kester, Mark; Mont, Michael A. (The Journal of Knee Surgery, 2014)
Additive manufacturing is an industrial technology whereby three-dimensional visual computer models are fabricated into physical components by selectively curing, depositing, or consolidating various materials in consecutive layers. Although initially developed for production of simulated models, the technology has undergone vast improvements and is currently increasingly being used for the production of end-use components in various aerospace, automotive, and biomedical specialties. The ability of this technology to be used for the manufacture of solid-mesh-foam monolithic and coated components of complex geometries previously considered unmanufacturable has attracted the attention of implant manufacturers, bioengineers, and orthopedic surgeons. Currently, there is a paucity of reports describing this fabrication method in the orthopedic literature. Therefore, we aimed to briefly describe this technology, some of the applications in other orthopedic subspecialties, its present use in hip and knee arthroplasty, and concerns with the present form of the technology. As there are few reports of clinical trials presently available, the true benefits of this technology can only be realized when studies evaluating the clinical and radiographic outcomes of cementless implants manufactured with additive manufacturing report durable fixation, less stress shielding, and better implant survivorship. Nevertheless, the authors believe that this technology holds great promise and may potentially change the conventional methods of casting, machining, and tooling for implant manufacturing in the future.
Keywords: arthroplasty; technology; manufacturing